The political ideology of Islam as expounded by Imam Al-Mawardi and its practical implementation in Indonesia - Ramadhan, Farhan Arif; Maulia, Shepti; Al Alif, Muamar Zahwa; Salsabila, Fatikha; Faiza, Atika Nur (Eduvest - Journal of Universal Studies, 2025)
This study explores the political ideology of Imam al-Mawardi as presented in "Al-Ahkam as- Sulthaniyyah" and its relevance to contemporary politics in Indonesia. The aim of the research is to understand how al-Mawardi's proposed political principles can be applied in the context of modern leadership. Utilizing text analysis through historical and anthropological approaches, the study evaluates the political movement initiated by al-Mawardi. The findings indicate that every leader must meet six essential criteria according to al-Mawardi: embracing and integrating religion as a moral force, possessing charismatic leadership qualities, ensuring fair treatment for all individuals, guaranteeing equal protection for everyone, promoting sustainable land productivity, and providing people with hope for their survival. These six characteristics are considered highly relevant for effective leadership in Indonesia, demonstrating that al-Mawardi's principles can offer valuable guidance for modern leaders.